Co-simulation and Operating Characteristic Analysis of Shift Clutch based on Recur Dyn and AMESim - Hao Chiyu; Feng Guangbin; Sun Huagang; Liu Qi (Jixie chuandong, 2018)
Based on the operating principle and cushioning characteristic of a shift clutch,the mechanical model of the shift clutch and the hydraulic model of the buffer circuit are respectively established in Recur Dyn and AMESim,then the mechanical-hydraulic co-simulation is realized through the software interface. The operating characteristics of the shift clutch with buffer circuit are analyzed,then the reliability is tested and the typical factors that affected the performance are explored. The basis for the failure mechanism and maintenance of the shift clutch is provided.